Sodium bicarbonate and feed flavor supplements for calves fed forage sorghum silage - Bolsen, K.; Axe, D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
High-moisture forage sorghum silage was fed to 108 steer calves to measure the effect of sodium bicarbonate and feed flavor (Omniflavor®) on calf performance. Overall performance was similar for all three rations by the end of the 94-day trial, but at days 29 to 56, when weather conditions were extremely cold, bicarbonate and Omniflavor each gave improved rate and efficiency of gains.
Keywords: Beef; Sodium bicarbonate; Sorghum silage; Rate of gain; Performance